2007
DOI: 10.1096/fj.06-7580com
|View full text |Cite
|
Sign up to set email alerts
|

Activation of apoptosis signal regulating kinase 1 (ASK1) and translocation of death‐associated protein, Daxx, in substantia nigra pars compacta in a mouse model of Parkinson's disease: protection by α‐lipoic acid

Abstract: Parkinson's disease (PD), a neurodegenerative disorder, causes severe motor impairment due to loss of dopaminergic neurons in substantia nigra pars compacta (SNpc). MPTP, a neurotoxin that causes dopaminergic cell loss in mice, was used in an animal model to study the pathogenic mechanisms leading to neurodegeneration. We observed the activation of apoptosis signal regulating kinase (ASK1, MAPKKK) and phosphorylation of its downstream targets MKK4 and JNK, 12 h after administration of a single dose of MPTP. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 40 publications
8
97
0
Order By: Relevance
“…6). [wt]DJ-1 abolished nuclear export of FLAG/Daxx under these conditions (Fig. 6), consistent with previous reports in cell culture and mouse models (24,39). In contrast, the PD-associated mutant [M26I]DJ-1 lost nuclear retention of FLAG/Daxx, leading to highly significant nuclear export of Daxx into the cytosol, where it is known to promote cell death (40).…”
Section: Pd-associated [M26i]dj-1 Constitutivelysupporting
confidence: 90%
“…6). [wt]DJ-1 abolished nuclear export of FLAG/Daxx under these conditions (Fig. 6), consistent with previous reports in cell culture and mouse models (24,39). In contrast, the PD-associated mutant [M26I]DJ-1 lost nuclear retention of FLAG/Daxx, leading to highly significant nuclear export of Daxx into the cytosol, where it is known to promote cell death (40).…”
Section: Pd-associated [M26i]dj-1 Constitutivelysupporting
confidence: 90%
“…Previously, DJ-1 has been shown to protect cells from apoptosis through sequestering Daxx in the nucleus, thereby inhibiting Daxx-induced apoptosis (6,22). In the present study, we found that nuclear, but not cytoplasmic, expression of DJ-1 was positively associated with nuclear expression of Daxx, suggesting that DJ-1 might promote ESCC progression through the same mechanism.…”
Section: Dj-1 Is An Independent Predictor For Escc Patientsupporting
confidence: 64%
“…Recently, DJ-1-mediated apoptosis has been shown to be attributed by its ability to interact with Daxx, the death-associated protein, and retain Daxx in nuclear localization (6,22). In this study, we found that nuclear DJ-1 (r = 0.296; P = 0.01) but not cytoplasmic DJ-1 (r = 0.079; P = 0.501) or combined DJ-1 score (r = 0.244; P = 0.057) was significantly associated with nuclear expression of Daxx (Fig.…”
Section: Dj-1 Expression In Different Esophageal Specimensmentioning
confidence: 99%
“…Apoptotic induced oxidative stress in conjunction with processes of mitochondrial dysfunction can contribute to a variety of disease states such as diabetes, ischemia, general cognitive loss, Alzheimer's disease, and trauma (Chong et al, 2005e;f;Harris et al, 2007;Leuner et al, 2007;Okouchi et al, 2007). Oxidative stress can lead to apoptosis in a variety of cell types that involve neurons, ECs, cardiomyocytes, and smooth muscle cells through multiple cellular pathways Harris et al, 2007;Kang et al, 2003b;Karunakaran et al, 2007;Verdaguer et al, 2007).…”
Section: Epo and Cellular Oxidative Stressmentioning
confidence: 99%